LINC-15. OUTCOME OF CHINESE CHILDREN WITH MEDULLOBLASTOMA: A MULTI-CENTER EXPERIENCE WITH RISK-ADAPTED THERAPY. (4th December 2020) - Sun, Xiaofei; Liu, Anthony Pak-Yin; Yang, Qunying; Wang, Jian; Wu, Shaoxiong; Zhen, Zijun; Wang, Jingsheng; Guo, Haixia; Jiang, Lian; Ma, Xiaoli; Weng, Wenjun; Yang, Lihua; et al.
Abstract: BACKGROUND: Medulloblastoma is the commonest brain tumor in young children but literature on Chinese is scarce. We hereby present the outcome of children with medulloblastoma managed according to a risk- and age-stratified guideline from ten institutions across China. METHODS: Patients <18 years of age diagnosed with medulloblastoma between January 2016 and April 2019 were reviewed. Patients ≥3 years, stratified into average-risk (≤1.5cm 2 residual tumor, non-metastatic, non-anaplastic histology) and high-risk (others) groups, were treated with risk-adapted craniospinal irradiation (average-risk: 23.4Gy, high-risk: 36Gy), tumor boost, and chemotherapy (lomustine/cisplatin/vincristine). Patients <3 years (considered high-risk, other than patients with localized and desmoplastic/nodular histology) received chemotherapy (cyclophosphamide/vincristine, high-dose methotrexate, carboplatin/etoposide) with/without delayed irradiation. RESULTS: 112 patients were included with a median age at diagnosis of 6.5 years (range: 0.5–16.7). 16 patients (14.3%) had residual tumor >1.5cm 2 and 36 (32%) had metastasis. Available data on histological subtype (n=87) were classic in 56 (64%), desmoplastic/nodular or extensive nodularity in 23 (26%), and large cell/anaplastic in 8 (9%). Molecular subgrouping (n=55) assigned tumors as WNT-activated (n=8, 15%), SHH-activated (n=17, 31%), Group 3 (n=12, 22%) and Group 4 (n=18, 33%). Respective 2-year EFS/OS for patients ≥3 and <3 years were 86.0±4.0%/96.4±2.1% and 57.8±12.6%/81.4±9.8% (EFS/OS p<0.001/p=0.009). Significant difference in outcome was also observed between patients with average-risk and high-risk disease (EFS/OS p=0.006/p=0.018). CONCLUSION: We demonstrated feasibility in protocolizing the inter-disciplinary treatment for medulloblastoma in China. This will serve as a prototype for the standardization of pediatric neuro-oncology care in the country.